2018
DOI: 10.26508/lsa.201800078
|View full text |Cite
|
Sign up to set email alerts
|

Co-existing feedback loops generate tissue-specific circadian rhythms

Abstract: The analysis of tissue-specific data-based models of the gene regulatory network of the mammalian circadian clock reveals organ-specific synergies of feedback loops.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 64 publications
4
61
0
Order By: Relevance
“…This emphasizes the biological relevance of our bifurcation analyses [41]. A recent study by Pett et al [45] suggested that different interlocked feedback loops might coexist and generate tissue-specific circadian rhythms. Taken together, the findings of potential tissue-specific clocks with the conditions under which nonlinear phenomena occur might contribute to the further understanding of organismic circadian desynchronization.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This emphasizes the biological relevance of our bifurcation analyses [41]. A recent study by Pett et al [45] suggested that different interlocked feedback loops might coexist and generate tissue-specific circadian rhythms. Taken together, the findings of potential tissue-specific clocks with the conditions under which nonlinear phenomena occur might contribute to the further understanding of organismic circadian desynchronization.…”
Section: Discussionsupporting
confidence: 53%
“…These clock proteins interact with each other by different positive and negative feedback loops, including the BMAL1-REVERB loop in addition to the wellknown PER-CRY loop [25,[41][42][43]. Interestingly, several studies have pointed to the fact that the relevance of specific loops in rhythm generation might be tissue-dependent [44][45][46]. The growing pool of identified regulators for circadian oscillations and their corresponding feedback loops stress the fundamental importance of synergistic loops, that seem to confer robustness to the clock [35].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in mammals, clock cells located in the suprachiasmatic nucleus (SCN) drive rhythms in peripheral tissues across the body via neural and humoral signals [1,14]. Peripheral tissues have the same clock network as in the SCN [15,16], although the relative importance of each circuit component may vary between tissues [17]. In plants, studies of synchronization [5,[18][19][20][21][22][23], grafting experiments [22], and the use of tissue-specific promoters [10] suggest that cell-cell communication is also important for coherent rhythms.…”
Section: Introductionmentioning
confidence: 99%
“…Such a Goodwin model was motivated by self-inhibition of the Period and Cryptochrome genes and the Bmal1-Rev-erba loop. However, in contrast to previous models [15,22,52,53], we did not fit the models to specific expression data. This implies that our models, while not quantitative in detail, can nevertheless be applicable in a wider context including in organisms other than mammals.…”
Section: Modeling Can Be Applied On Different Levelsmentioning
confidence: 96%